THE SYNTACTIC STRUCTURE AND FUNCTIONAL ROLE OF COMPOUND SENTENCES IN THE ENGLISH GRAMMAR ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth exploration of compound sentences in the English language, covering their definition, structure, and use in writing. A compound sentence combines two or more independent clauses, which can stand alone as complete thoughts but are linked to enhance meaning and coherence. The article explains the main ways to structure compound sentences—using coordinating conjunctions (e.g., FANBOYS), semicolons, or conjunctive adverbs—and discusses the purpose each structure serves. Additionally, common mistakes, such as comma splices and run-on sentences, are addressed to help readers avoid common pitfalls. Through examples and explanations, this piece emphasizes the importance of compound sentences in creating clear, varied, and engaging writing. The conclusion highlights the value of mastering this sentence structure to strengthen written communication.